Application of ultraviolet light assisted titanium dioxide photocatalysis for food safety: A review. (December 2016) - Ramesh, Tamanna; Nayak, Balunkeswar; Amirbahman, Aria; Tripp, Carl P.; Mukhopadhyay, Sudarsan
Abstract: UV-assisted TiO2 photocatalysis (TUV) is an emerging non-thermal technology that has shown to efficiently inactivate food-borne pathogens. While TUV processing has been a well-established technique for water and wastewater treatment, its application in the food industry is minimal. The basic working principle underlying TUV technology is the photocatalytic production of reactive oxygen species (ROS) that carry out redox reactions with species adsorbed on the TiO2 surface. Studies have confirmed that severe cell damage including destruction of the cytoplasmic membrane, super-coiled plasmid DNA and genomic DNA, and internal organelles occurred when bacteria were exposed to TUV. Recently, TUV has been explored for its applications in surface disinfection and post-harvest disease control of fresh produce, pasteurization of beverages, and anti-microbial food packaging. Although the novel developments in the technology are promising, more research is needed to achieve the practical application of this technology. The intent of this article is to provide an overview of the principles of TUV, the mechanism of microbial inactivation by TUV, and the recent findings on utilization of TUV for microbiological safety of foods and also, to present the prospective opportunities for TUV in the food industry. Industrial relevance: TUV is a non-thermal technique recently explored for food safety applications. This review presents the prospective opportunities of TUV treatment in food industries in the area of food preservation. Based on the existing research findings discussed in this article, the authors have recommended major research aspects that are necessary to understand the scope of TUV technology in the food industry and validate the technology. This background will provide the necessary information for food scientists as well as industries to work on optimizing the treatment with regard to food quality and safety. Latest findings of TUV technology are promising; yet, more work is needed to develop and integrate extensive information for the practical application of this technology in the food industry. The areas that need more attention are listed and critically reviewed to facilitate utilization of the TUV technology in the food industry. Highlights: TUV can be used for surface disinfection and post-harvest disease control of fresh produce. TiO2 coated packaging materials have shown antimicrobial properties. Limited validation studies of TUV for microbiological food safety applications. Consumer perceptions on residual TiO2 in TUV treated foods is important for scale up of the technology.